Integrated Islamic Schools as Sites of Everyday Cultural Resistance: An Ethnographic Study of Urban Muslim Education in Indonesia - Basalamah, Qonitah (Universitas Islam Negeri Ar-Raniry Banda Aceh, Aceh, Indonesia., 2026)
This study examines Integrated Islamic Schools (Sekolah Islam Terpadu, SIT) as sites of everyday cultural resistance in urban Indonesia. Drawing on a year-long school ethnography at SIT Nurul Fikri Depok, this research applies James C. Scott’s framework of everyday resistance to analyze how cultural boundaries and moral orders are produced through routine institutional practices. The findings show that cultural resistance is enacted not through overt confrontation but through the disciplined organization of school environments, behavioral norms, and symbolic practices. The study identifies three interconnected mechanisms through which this resistance operates: strategic parental school choice, the internalization of discipline through the moral environment and staff formation, and the cultivation of a coherent Islamic habitus through repeated practices and shared moral reasoning. These mechanisms demonstrate how schools function as arenas of cultural formation where identity, authority, and moral boundaries are negotiated in everyday life. By foregrounding micro-level practices, this research contributes to the sociology of education and Islamic studies by clarifying how cultural resistance is embedded in routine institutional life. The study highlights the significance of schooling as a site where broader ideological projects are translated into lived social realities within contemporary Muslim societies. Abstrak Penelitian ini mengkaji Sekolah Islam Terpadu (SIT) sebagai arena resistensi kultural sehari-hari dalam konteks masyarakat urban Indonesia. Berdasarkan etnografi sekolah yang dilakukan selama satu tahun di SIT Nurul Fikri Depok, studi ini menggunakan kerangka resistensi sehari-hari James C. Scott untuk menganalisis bagaimana batas-batas kultural dan tatanan moral diproduksi melalui praktik-praktik institusional yang rutin. Temuan penelitian menunjukkan bahwa resistensi kultural tidak diwujudkan melalui konfrontasi terbuka, melainkan melalui pengorganisasian lingkungan sekolah secara disipliner, pembentukan norma perilaku, dan praktik simbolik. Studi ini mengidentifikasi tiga mekanisme yang saling berkaitan dalam proses tersebut, yaitu pilihan sekolah strategis oleh orang tua, internalisasi disiplin melalui lingkungan moral dan pembentukan staf, serta pembudayaan habitus Islam melalui praktik yang berulang dan penalaran moral bersama. Mekanisme-mekanisme ini memperlihatkan bagaimana sekolah berfungsi sebagai arena pembentukan kultural, di mana identitas, otoritas, dan batas-batas moral dinegosiasikan dalam kehidupan sehari-hari. Dengan menyoroti praktik-praktik mikro, penelitian ini berkontribusi pada kajian sosiologi pendidikan dan studi Islam dengan menjelaskan bagaimana resistensi kultural tertanam dalam kehidupan institusional yang rutin. Studi ini menegaskan signifikansi pendidikan sebagai ruang di mana proyek-proyek ideologis yang lebih luas diterjemahkan ke dalam realitas sosial yang hidup dalam masyarakat Muslim kontemporer.